Characterizing Mobility and its Association with HIV Outcomes in Refugee Settlements in Uganda - Robin E. Klabbers; Canada Parrish; Patient Iraguha; Marcel Kambale Ntuyenabo; Scovia Ajidiru; Valentine Nshimiyimana; Kampire Caroline; Zikama Faustin; Elinor M. Sveum; Timothy R. Muwonge; Kelli N. O'Laughlin (Ubiquity Press, 2024)
Background: A better understanding of refugee mobility is needed to optimize HIV care in refugee settlements. Objectives: We aimed to characterize mobility patterns among people living with HIV in refugee settlements in Uganda and evaluate the association between mobility and retention in HIV care. Methods: Refugees and Ugandan nationals accessing HIV services at seven health centers in refugee settlements across Uganda, with access to a phone, were recruited and followed for six months. Participants received an intake survey and monthly phone surveys on mobility and HIV. Clinic visit and viral suppression data were extracted from clinic registers. Mobility and HIV data were presented descriptively, and an alluvial plot was generated characterizing mobility for participants' most recent trip. Bivariate Poisson regression models were used to describe the associations between long-term mobility (≥1 continuous month away in the past year) and demographic characteristics, retention (≥1 clinic visit/6 months) and long-term mobility, and retention and general mobility (during any follow-up month: ≥2 trips, travel outside the district or further, or spending >1-2 weeks (8-14 nights) away). Findings: Mobility data were provided by 479 participants. At baseline, 67 participants (14%) were considered long-term mobile. Male sex was associated with an increased probability of long-term mobility (RR 2.02; 95%CI: 1.30-3.14, p < 0.01). In follow-up, 185 participants (60% of respondents) were considered generally mobile. Reasons for travel included obtaining food or supporting farming activities (45% of trips) and work or trade (33% of trips). Retention in HIV care was found for 417 (87%) participants. Long-term mobility was associated with a 14% (RR 0.86; 95%CI: 0.75-0.98) lower likelihood of retention (p = 0.03). Conclusions: Refugees and Ugandan nationals accessing HIV care in refugee settlements frequently travel to support their survival needs. Mobility is associated with inferior retention and should be considered in interventions to optimize HIV care.